HUBUNGAN DUKUNGAN ORANG TUA DENGANKECEMASAN PADA ANAK USIA SEKOLAH PADA SAAT AKAN DILAKUKAN PEMASANGAN INFUS DI RSUP PROF. DR. R. D. KANDOU MANADO - Yanni, Iloh Devi; Umboh, Adrian; Ismanto, Amatus Yudi (JURNAL KEPERAWATAN, 2017)
Abstract :Psychological support of parents potentially affect the health status of the child as if the child support system is less then the child will be prone to anxiety. Objective: Unknown Parents support relationship with anxiety in children of school age at the time will be the installation of a drip. Methods: observational analytic method, do is cross sectional approach. Population is the research object or object under study. The number of children treated in the Emergency Room of the Child in September 2016 was 151 children. The sample is part of a whole object under study and are considered representative of the entire population. So the sample: in this study is 45 parents and children who are being treated at Children's Emergency Room. Results Based on the results using a statistical test Chi-Square, the value p value = 0,010. The p-value is less than the value Î± (Î± = 0.05) Conclusion : that there is a relationship between anxiety support parents with school-age children. Suggestions : As an input for parents in order to increase support for children during infusion is done so that children can be more at ease when performed invasive procedures. Keywords: Parental Support, School Age Children, Anxiety. Abstrak : Dukungan psikologis orang tua berpotensi mempengaruhi status kesehatan anak seperti apabila sistem dukungan anak kurang maka anak akan cenderung mudah mengalami cemas. Tujuan Penelitian : Diketahui hubungan dukungan Orangtua dengan kecemasan pada anak usia sekolah pada saat akan dilakukan pemasangan infus. Metode : metode observasional analitik, pendekatan dilakukan adalah cross sectional. Populasi adalah keseluruhan objek penelitian atau objek yang diteliti. Jumlah anak yang dirawat di Instalasi Rawat Darurat Anak pada bulan September 2016 adalah 151 orang anak. Sampel adalah sebagian dari keseluruhan objek yang diteliti dan dianggap mewakili seluruh populasi. Jadi sampel dalam penelitian ini yaitu 45 orang tua dan anak yang sedang dirawat di Instalasi Rawat Darurat Anak. Hasil PenelitianBerdasarkan hasil uji statistik menggunakan Chi- Square, diperoleh nilai pvalue = 0,010. Nilai p ini lebih kecil dari nilai Î± (Î± = 0,05)Kesimpulan bahwa terdapat hubungan antara dukungan Orangtua dengan kecemasan pada anak usia sekolah. Saran Sebagai bahan masukan bagi orang tua agar dapat meningkatkan dukungan kepada anak saat dilakukan pemasangan infus sehingga anak dapat lebih tenang ketika dilakukan prosedur invasive. Kata Kunci : Dukungan Orang Tua, Anak Usia Sekolah, Kecemasan.